Monolingual Pedagogy in a Multilingual Context: Challenges and Paradigm Shifts in English Language Teaching - Cinamula Kashuli Joachim; Mukuna Tshimpela Robert; Tembue Matthieu Zembele; Bapolisi Bahuga Paulin; Buzigire Mufanzara Bertin (Universitas Galuh, 2026)
This paper explores 1) the challenges that emerge when using monolingual pedagogy in multilingual contexts in the teaching of English as a foreign language ; and 2) discusses the problems faced by the learners in understanding syntactic contents of language and suggests remedial teaching measures. This survey study involved second year students of English at ISP BUKAVU and employed questionnaires to collect the data. The finding shown in the reality is that participants answered in French instead of using the English language, resulting the fact that they happen to grasp the message but it is hard for them to convey it in the target language. In this condition, translanguaging is a new approach that was be used to enhance the mastery of syntactic rules. Monolingual pedagogy works in some contexts but in a multilingual context as experienced by the second year students of English at ISP BUKAVU, translaguaging marks its valuable and still can assist the learners to improve their knowledge of English if teachers of English subsequently and reasonable use it. This findings advocates for a paradigm shift towards translanguaging to enhance learning outcomes in multilingual classrooms as proved throughout the data used in the present paper. The analysis of meaning in words, phrases, and sentences is suggested for further research.